Performance Budgeting-Is Accrual Accounting Required? - Diamond, Jack (IMF Working Papers; Working Paper ;, 2002)
This paper reviews the role of accounting in budget system reform from the perspective of emerging economies who wish to adopt the OECD's performance budgeting reforms. While many OECD countries, pursuing the reforms associated with the New Public Management, have moved their accounting systems from a cash to an accrual basis, this paper argues that given the costs involved, such a move is perhaps only worthwhile in the context of adopting much wider public sector management reforms. Moreover, while recognizing that accrual accounting does support public expenditure management best practices, it is also argued that many of the objectives of performance-oriented budgeting can be attained by less than full accrual accounting, and that unless certain preconditions are met it is safer for countries to remain with, and improve, their cash-based accounting systems. For those countries with sound enough cash-based systems the paper describes a possible phased approach to the introduction of accruals, as well as the parallel stages of adopting the new international GFSM 2001 reporting requirements.